The city is ours : spaces of political mobilization and imaginaries of nationhood in Turkey - Güvenç, Muna (Cornell University Press, 2024)
"The City Is Ours provides a critical account of how the pro-Kurdish party's urban politics in the early 2000s fostered the rise of Kurdish nationhood and political mobilization in Diyarbakır, Turkey"--